A Minimal Light‐Driven System to Study the Enzymatic CO2 Reduction of Formate Dehydrogenase. Issue 24 (29th November 2022) - Laun, Konstantin; Duffus, Benjamin R.; Kumar, Hemant; Oudsen, Jean‐Pierre H.; Karafoulidi‐Retsou, Chara; Tadjoung Waffo, Armel; Hildebrandt, Peter; Hoang Ly, Khoa; Leimkühler, Silke; Katz, Sagie; Zebger, Ingo
Abstract: A minimal light‐driven approach was established for studying enzymatic CO2 conversion spectroscopically. The system consists of a photosensitizer Eosin Y, EDTA as a sacrificial electron donor and substrate source, and formate dehydrogenase from Rhodobacter capsulatus ( Rc FDH) as a biocatalyst. This simplified three‐component system provides a photo‐triggered control for in situ characterization of the entire catalytic reaction. Direct reduction of Rc FDH by the photosensitizer without additional electron carriers was confirmed via UV‐Vis spectroscopy, while GC‐MS and IR spectroscopy were used to follow photoinduced CO2 generation from EDTA and its subsequent enzymatic reduction, yielding the product formate. Photo‐driven and in vitro, dye‐based CO2 reduction was inhibited by azide under a mixed (competitive‐non‐competitive) inhibition mode. IR spectroscopy reveals displacement of the competitively‐bound azide by CO2, reflecting an interaction of both with the active site cofactor. This work comprises a proof‐of‐concept for a new approach to employ light for regulating the reaction of formate dehydrogenases and other CO2 reductases. Abstract : Enzymatic CO2 reduction : Most photocatalytic systems contain natural electron acceptors as mediators. The minimal photocatalytic unit reported herein bypasses such additional redox mediators and donates electrons directly into the enzyme. A formate dehydrogenase was used as electron acceptor for the photocatalytic conversion of CO2 to formate. An essential component of the light‐driven minimal system is EDTA, which serves as CO2 source for the enzyme and sacrificial electron donor for the photosensitizer.